A light-cone catalogue from the Millennium-XXL simulation: improved spatial interpolation and colour distributions for the DESI BGS. Issue 3 (8th September 2022) - Smith, Alex; Cole, Shaun; Grove, Cameron; Norberg, Peder; Zarrouk, Pauline
ABSTRACT: The use of realistic mock galaxy catalogues is essential in the preparation of large galaxy surveys, in order to test and validate theoretical models and to assess systematics. We present an updated version of the mock catalogue constructed from the Millennium-XXL simulation, which uses a halo occupation distribution method to assign galaxies r -band magnitudes and g − r colours. We have made several modifications to the mock to improve the agreement with measurements from the SDSS and GAMA surveys. We find that cubic interpolation, which was used to build the original halo light cone, produces extreme velocities between snapshots. Using linear interpolation improves the correlation function quadrupole measurements on small scales. We also update the g − r colour distributions so that the observed colours better agree with measurements from GAMA data, particularly for faint galaxies. As an example of the science that can be done with the mock, we investigate how the luminosity function depends on environment and colour, and find good agreement with measurements from the GAMA survey. This full-sky mock catalogue is designed for the ongoing Dark Energy Spectroscopic Instrument Bright Galaxy Survey, and is complete to a magnitude limit r = 20.2.